Education for entrepreneurship and social innovation (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2025)
The changes occurring in society and the world must be taken into account by universities, which should not remain passive but participate actively. The public policies implemented in Venezuela at the educational level revolve around the universalization of knowledge, cultural identity, and the pursuit of greater social equity to achieve the common good. This underscores the importance of generating cooperative and self-management activities for the sustainable development of communities, representing an opportunity for universities to develop training plans that enable active participation in transforming their environment through the application of knowledge to solve social problems. Entrepreneurial education is defined as the educational approach that fosters the growth of students' entrepreneurial potential and contributes to their holistic development, primarily in intellectual, societal, and moral dimensions, beyond socio-economic and labor growth.
Keywords: university entrepreneurship; entrepreneurial education; sustainable development; social innovation